2014
DOI: 10.4236/ojms.2014.42008
|View full text |Cite
|
Sign up to set email alerts
|

Cell Size Dependent Responses of Phytoplankton Assemblages to Nitrate and Phosphate Additions in Surface Waters of the Northern South China Sea

Abstract: Bioavailability of nitrogen (N) and phosphorus (P) is known to affect marine phytoplankton physiology, thus influencing their primary productivity; and it's of general interest to see how the N or/and P additions affect the differently cell-sized phytoplankton assemblages. Data from the northern South China Sea showed that P addition increased up to 6 times of total chl a content within 24 h in the estuarine water; and N+P addition increased more than 20 times of chl a within 144 h in the pelagic water. The P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In the field, differently cell-sized phytoplankton assemblies usually have differential responses to environmental variables, including nutrients [18,34], light [4,29], and their interactions [49]. Here, we showed that the upward-shifted light insignificantly affected the growth of the small T. pseudonana, but reduced that of the large T. punctigera, resulting from the differential effects upon the cellular compositions, photosynthesis, and antioxidant abilities (Figure 7).…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…In the field, differently cell-sized phytoplankton assemblies usually have differential responses to environmental variables, including nutrients [18,34], light [4,29], and their interactions [49]. Here, we showed that the upward-shifted light insignificantly affected the growth of the small T. pseudonana, but reduced that of the large T. punctigera, resulting from the differential effects upon the cellular compositions, photosynthesis, and antioxidant abilities (Figure 7).…”
Section: Discussionmentioning
confidence: 68%
“…Perhaps the culture time was still not long enough for the smaller T. pseudonana to adapt completely to such a harsh light shift, although the photosynthetic capacity was already steady (Figure S1). Yi et al [34] also recognized that the small cell-dominated phytoplankton assemblages respond much slower to nutrient addition than large cell-dominated phytoplankton assemblages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations